We were kings - O'Malley, Thomas, 1967-; Purdy, Douglas Graham (Little, Brown and Company, 2016)
In 1950's Boston, the Irish Republican Army is running guns and killing witnesses. Cal and Dante are committed to stopping them. When a body is discovered at the Charlestown locks--tarred, feathered and shot to death--it appears to be a gangland killing, and is almost immediately dismissed. However, Cal O'Brien's cousin, Boston PD detective Owen Lackey, recognizes the murder style as the typical retribution for IRA informers. Combined with a tip-off about a boat coming into Boston weighed down with stolen guns and ammunition, the body in the locks hints that much more may be at stake than a one-off hit.